A new method of relative measures as applied to anthropological material - Rysiewski, Henryk (Anthropological Review, 1975)
In this paper anthropological quotient indices were subjected to criticism. If in a set of m measurements (P) one undergoes change, m – 1 quotient indices calculated on the basis of m measurements will be changed (when total number of these indices is 0,5 (m2 – m)). In the new method as the parameter of given set of data for each individual the mean value of all its measurements is taken. The proposed indices (Wr) are the percentage values of particular measurement when above parameter is equal 100. Values of relative indices (Wr) are not influenced by size of the individual. Moreover calculation of Wr requires less effort than Wi The author has illustrated how Wr works in comparison with Wi and crude measurements (P) on the basis of skull series from Złota Pińczowska, district Pińczów.